INTEGRATING FABLE VIDEO VIA YOUTUBE TO ENHANCE EFL STUDENTS’ LISTENING SKILL - Wardani, Debby Kusuma; Nuraini, Kristi; Fatkurochman, Henri (Universitas Muhammadiyah Metro, 2025)
Listening becomes one of the skills that is very important to master. Unfortunately, many EFL students lack in listening. This study aimed to help EFL students develop their listening skills by integrating fable videos. This research used classroom action research. The participants of this study consist of 31 tenth-grade 3 students at SMAN Arjasa, Jember. The instruments used by the author were an observation checklist and a listening test, and to collect the data, the author observed the students in every cycle of cycle 1 and 2, and also conducted the listening test at the end of each cycle. The data were analyzed by classification and scoring. The use of fable video as the media significantly improved students’ listening comprehension and became an effective tool that can engage students' participation during the learning process, also understandable within the context existing in the video. The use of interactive and effective media, such as fable video, is really needed to improve students' listening skills and participation.